HIV/HCV Co‐infection: Overcoming Barriers to Treatment. (July 2016) - Gross, Chloe; Akoth, Elizabeth; Price, Angie; Kattakuzhy, Sarah; Silk, Rachel; Rosenthal, Elana
Abstract : A critical step in the eradication of hepatitis C virus (HCV) infection is access to effective therapy. With the advent of interferon‐free regimens, HCV providers and patients gained hope that the success seen in clinical trials could be translated to the real world. However, the exorbitant cost of the new direct‐acting antivirals limits access to these medications to the general HCV population, especially underserved patients with public insurance. We used a descriptive qualitative approach to detail the measures necessary and challenges faced by an inner‐city nursing team in Washington, DC to obtain the new direct‐acting antivirals. Significant time and dedication on the part of providers and staff was required to assist patients with the process of obtaining direct‐acting antivirals.